The correlation of the molecular structure of polyolefins with environmental stress cracking resistance - Shebani, Anour Nasser (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2006.